Changes of inflammation-associated cytokine expressions during early phase of experimental endotoxic shock in macaques - Ji, Xiao-Hui (World J Gastroenterol, 2004)
AIM: To study changes of inflammation-associated cytokine expressions during early phase of endotoxic shock in macague. METHODS: Experiments were performed in Macaque mulatta treated with LPS 2.8 mg/kg in shock model group or with normal saline in control group. Blood samples were collected before, or 60 min, or 120 min after LPS injection, respectively. Liver and spleen tissues were obtained at 120 min after LPS injection. The plasma levels of TNF-α , IL-1 β , IL-10 and IL-12P40 were determined by double-antibody sandwich ELISA with antibodies against human cytokines. The mRNA levels of TNF-α , IL-1 β , and IL-18 in peripheral blood mononuclear cells (PBMCs), liver and spleen were examined by real-time fluorescence semi-quantitative RT-PCR with the primers based on human genes. RESULTS: Mean systemic arterial pressure (MAP), systemic vascular resistance index (SVRI) and left ventricular work index (LVWI) of macaques were significant declined in shock model group on average 60 min after LPS injection. The plasma levels of TNF-α and IL-10 were significantly increased 60 min after LPS injection and then decreased. The plasma levels of IL-1 β and IL-12P40 were significantly increased at 120 min after LPS injection. The mRNA levels of TNF-α and IL-1 β were significantly increased 60 min after LPS stimulation in PBMCs and 120 min after LPS stimulation in livers. The mRNA level of IL-18 was significantly increased 120 min after LPS stimulation in PBMCs and livers. But in spleen, only TNF-α mRNA level in LPS group was significantly higher 120 min after LPS stimulation, compared with that in control group. CONCLUSION: An endotoxic shock model of Macaque mulatta was successfully established. Both antibodies for ELISA and PCR primers based on human cytokine assays were successfully applied to detect macaque cytokines. In the model, inflammatory cytokines, such as TNF-α , IL-1 β , IL-12 and IL-18 as well as anti-inflammation cytokine IL-10, were released at very early phase of endotoxic shock within 120 min after LPS injection. PBMCs and liver cells might be the important sources of these cytokines.